Proximity to Major Roadways is a Risk Factor for Airway Hyper-Responsiveness in Adults - Shannon Riley; Julie Wallace; Parameswaran Nair (Canadian Respiratory Journal)
BACKGROUND: Proximity to major roads is reported to be associated with asthma and airway hyper-responsiveness in children. Similar studies using objective measurements in adults are not available in Canada.